The Mali Elephant Project: protecting elephants amidst conflict and poverty - Canney, S (Wiley, 2019)
This short report shows how it has been possible to protect a small yet important, highly vulnerable, remnant population of desert-adapted African elephants Loxodonta africana that roams through a vast, populated area of Mali, which in recent years has become lawless and subject to an aggressive jihadist insurgency. Initial studies showed how ecosystem trends threatened elephant survival and local livelihoods, and exacerbated human–human and human–elephant conflict. A combination of adaptive management and action research methods was used to understand the social, economic, political and environmental aspects of this complex system. This knowledge served to derive intervention strategies that attempted to tackle the underlying drivers of threat to elephant survival. Central to this approach was the reinforcement of existing attitudes towards elephants and the use of collaborative methods. Local communities were empowered to counter resource over-exploitation and degradation by devising resource-management systems that were rooted in existing practice and provided tangible livelihood benefits from elephant conservation. When lawlessness overtook the elephant range in 2012, it became subject to attacks by armed groups, a deepening insurgency and elephant poaching. The existing community work proved key to respond to the escalation of poaching in 2015, as it had engaged local people in the conservation effort, improving their lives and securing local ‘buy-in’. This facilitated the work of the newly created anti-poaching unit, which was trained to operate according to an ‘intelligent’ and ethical doctrine that used local information to cope with the insecurity and target its efforts.